Răspunsuri

2014-11-12T00:22:28+02:00
A) 3×11√2 ×(12√2-2×5√2 -4√2)=
   =33√2×(12√2-10√2-4√2)
   =33√2×(-2√2)=
   = -66×2=-132
b) x√6-(3√2 +2√3) (3√2-2√3)
    x√6=(3√2)² - (2√3)²
    x√6=18-12
    x√6=6=6 pe √6 =6√6 pe 6=√6
am rationalizat cu √6
aa
multumesc:*
cu placere
ai gresit
2014-11-12T00:33:51+02:00
3√242=3√2√11²=3·11√2=33√2
√288=√2²√2²√3²√2=2·2·3√2=12√2
2√50=2√2√5²=2·5√2=10√2
√32=√2²√2²√2=2·2√2=4√2
33√2x(12√2-10√2-4√2)=33√2·(-2√2)=-66·2=-132

x/3√2+2√3-3√2-2√3/6=
x/3√2=3√2x/3²√2²=3√2x/18=√2x/6
√2x/6+2√3-3√2-√3/3=
√2x/6=-2√3+3√2+√3/3
√2x/6=(-6√3+9√2+√3)/3
√2x/6=(9√2-5√3)/3
3√2x=6(9√2-5√3)
3√2x=54√2-30√3
x=3(18√2-10√3)/3√2
x=(18√2-10√3)/√2
x=√2(18√2-10√3)/2
x=(18·2-10·2√3)/2
x=2(18-10√3)/2
x=18-10√3
x=2(9-5√3)